2013
DOI: 10.1016/j.yexmp.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of p66ShcA restores redox-sensitive stress response program in cisplatin-induced acute kidney injury

Abstract: Overwhelming oxidative stress and compromised tubular cell antioxidant response have been incriminated for cisplatin (Cis) -induced acute kidney injury (AKI). We hypothesized that Cis-induced KI was the outcome of the deactivated redox-sensitive stress response program (RSSRP). Wild (WT) and heterozygous p66ShcA+/− mice in groups of six were administered either normal saline (WT) or Cis (12.5 mg/kg, intraperitoneal, Cis/WT). Renal biomarkers were collected and kidneys were harvested for renal histology. Cis/WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Oxidative stress and mitochondrial dysfunction related to ATP depletion have been observed in response to cisplatin-induced cellular injury in the kidney ( Arany and Safirstein, 2003 ). Rattanavich et al (2013) reported that cisplatin treatment results in diminished expression of renal Mn-SOD via the enhanced expression of phospho-p66ShcA and phospho-Foxo3A in studies featuring heterozygous p66ShcA ( ± ) mice. Specifically, increased expression of phospho-p66ShcA and phospho-Foxo3A was detected in the renal tissue of wild-type mice treated with cisplatin in association with reduced expression of both Mn-SOD and catalase.…”
Section: Physiological Significance Of Manganese Superoxide Dismutasementioning
confidence: 99%
“…Oxidative stress and mitochondrial dysfunction related to ATP depletion have been observed in response to cisplatin-induced cellular injury in the kidney ( Arany and Safirstein, 2003 ). Rattanavich et al (2013) reported that cisplatin treatment results in diminished expression of renal Mn-SOD via the enhanced expression of phospho-p66ShcA and phospho-Foxo3A in studies featuring heterozygous p66ShcA ( ± ) mice. Specifically, increased expression of phospho-p66ShcA and phospho-Foxo3A was detected in the renal tissue of wild-type mice treated with cisplatin in association with reduced expression of both Mn-SOD and catalase.…”
Section: Physiological Significance Of Manganese Superoxide Dismutasementioning
confidence: 99%
“…The main side effect of cisplatin is AKI, with an incidence rate of 25% to 35%. Recent studies have shown that cisplatin-related AKI is caused by attenuated antioxidant effects [ 26 ]. Jung et al [ 27 ] found that SIRT1 can attenuate the mediated nephrotoxicity of platinum compounds.…”
Section: Role Of Sirt1 In the Kidney Diseasementioning
confidence: 99%
“…First mechanism, SIRT1 up-regulation can degrade excessive free radicals, so increase purine degradation, and lead to ATP generation thus can ameliorate AKI by inhibition of oxidative stress and the another mechanism, SIRT1 by up-regulating the number and function of mitochondria that have a direct effect on cell apoptosis, ATP synthesis, and maintains the normal cell and organ functions. Disturbance in Mitochondrial is an important factor for acute kidney disease that is caused by toxic substances or ischemia [39]. FSK significantly increased the SIRT1 mRNA in kidneys of rats.…”
Section: Discussionmentioning
confidence: 99%